A New İterative Algorithm on the Time-Fractional Fisher Equation: Residual Power Series Method - Al Qurashi, M.M.; Körpınar, Zeliha; Baleanu D.; Inc M. (SAGE Publications Inc., 2017)
In this article, the residual power series method is used to solve time-fractional Fisher equation. The residual power series method gets Maclaurin expansion of the solution. The solutions of present equation are computed in the shape of quickly convergent series with quickly calculable fundamentals using mathematica software package. Explanation of the method is given by graphical consequences and series solutions are made use of to represent our solution. The found consequences show that technique is a power and efficient method in conviction of solution time-fractional Fisher equation. © The Author(s) 2017.
Keywords: Residual power series method; series solution; time-fractional Fisher equation